2019
DOI: 10.1177/0021998319877454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective performance of hydrophobic coatings applied on carbon-fibre epoxy composites

Abstract: Carbon–fibre epoxy composites are widely used for high-performance structural applications, where they are often exposed to harsh environments. The result of moisture ingress has been extensively studied, causing significant deterioration in the mechanical properties of these composites. This study evaluates the performance of five commercial hydrophobic coatings as protective layers, to inhibit moisture ingress into the composite. The coatings evaluated were NeverWet, HydroBead, SHC, Aculon and LiquidGlass. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…With the addition of MP1100, the water contact angle of the composite material does not change significantly for the following reasons: first, another component of the composite material, short carbon fiber (SCFs), is hydrophobic, which affects the water contact angle on the surface of the composite material. A similar conclusion was also found in literature 53 . Second, the effective free radical concentration of COOH on the composite surface containing MP1100 is low, and its ability to change the surface contact angle is limited.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…With the addition of MP1100, the water contact angle of the composite material does not change significantly for the following reasons: first, another component of the composite material, short carbon fiber (SCFs), is hydrophobic, which affects the water contact angle on the surface of the composite material. A similar conclusion was also found in literature 53 . Second, the effective free radical concentration of COOH on the composite surface containing MP1100 is low, and its ability to change the surface contact angle is limited.…”
Section: Resultssupporting
confidence: 89%
“…A similar conclusion was also found in literature. 53 Second, the effective free radical concentration of COOH on the composite surface containing MP1100 is low, and its ability to change the surface contact angle is limited. In general, the influence of SCFs and h-BN on the water contact angle of the composite surface is greater than that of MP1100, resulting in little change in the water contact angle of the composite surface containing MP1100.…”
Section: Effect Of Mp1100 Content On Surface Wettability Of Ptfe Comp...mentioning
confidence: 99%
“…Compared to oxygen plasmas, the air plasma required mid to high powers (150 W) and short exposure times (60 s) to obtain improved mechanical performance. Similarly, O'Connor and Dowling [ 118 ] tested the improvement of adhesion of CF/epoxy composites after atmospheric air plasma pretreatment and concluded that air plasmas could activate the epoxy and thus improve abrasion resistance by increasing the surface energy of the composite substrate.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…However, different from hardness variation trends, the HDPE composites exhibit the maximum contact angle of 95.2 • when the content of SCFs is 20 wt %, which exhibits the hydrophobicity; the contact angle decreased to 93.5 while the content of SCFs continued increasing. The SCFs have a lower surface energy compared to the HDPE matrix and, thus, cause an increase in contact angle of HDPE composites [36]; nevertheless, the SCFs are prone to agglomeration when the concentration reaches 25 wt %, which might reduce the specific surface area of HDPE composites. As a result, the contact angle decreased.…”
Section: Effects Of Scfs On the Hardness And Wettability Of Hdpe Comp...mentioning
confidence: 99%